COMPETITIVE STRATEGY FORMULATION OF PT. TRANSPORTASI JAKARTA ON PUBLIC TRANSPORTATION SECTOR IN DKI JAKARTA DURING THE PANDEMIC OF COVID-19 (Case Study on PT.Transportasi Jakarta) - Belinda, Naurah (Jurnal Ilmiah Mahasiswa FEB, 2021)
Formulation of Strategy is a method that are used by the companies to achieve business goals by developing the competitive advantages that the business have. One of the factors that influence the strategy factor comes from two sources, namely internal and external factor of the business. This study aims to identify and analyse the internal and external environment of PT.Transportasi Jakarta, and to identify and analyse the competitive strategy. This study uses a qualitative method and using techniques such as observation, documentation, interviews and literature review for collection the data. the analysis used in this study to formulate a strategy for PT. Transportasi Jakarta are IFE EFE, CPM, SWOT M, IE M, GSM and QSPM. Based on the last results of the matrix analysis, it can be concluded that main strategy recommendation for facing the competition in the public transportation for PT. Transportasi Jakarta is market penetration tKeywords : Strategy Formulation, IFE, EFE, CPM, SWOT M, IE M, GSM, QSPM